Sistema audiovisual para mostrar información publicitaria en carritos de supermercados - García-Rodríguez, Juan Gabriel (Instituto Tecnológico de Costa Rica, 2012)
With this project what was achieved was to develop a prototype of a marketing system that is capable of integrating with the Cisco Systems call Digital Media Suite and impart information of all the different products by playing commercials. This system will want to locate in shopping carts and thereby gain the attention of each customer. The system includes a proximity detection system that works through the Bluetooth protocol and to identify what the product shelf nearest selected among other possible shelves, the video also shows for that specific product. The main feature of the system is that it enables you count the number of times you play a specific video and store it in an internal database, which is then synchronized with a HTML server application to display statistics for the sole purpose able to provide an advertising service to different brands of products that can be priced and thus generate an income to the supermarket company.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2012.
Keywords: Mercadeo; Cisco Systems; Digital Media Suite; Protocolo Bluetooth; Aplicaciones; Publicidad